Evaluasi Partisipasi Masyarakat dalam Penggunaan GPS (Kasus: Pengambilan Titik Koordinat Bambu di Desa Patanyamang): Evaluation of Community Participation in the Use of GPS (Case: Taking Bamboo Coordinate Points in Patanyamang Village) - Mukhlisa, Andi Nurul; Mirnawati; Asriany (Prodi Kehutanan Universitas Khairun, 2025)
Patanyamang Village, located in Camba District, South Sulawesi, is an area with a high potential for landslide risks. One of the disaster mitigation efforts carried out is mapping the distribution of bamboo plants as soil-retaining vegetation. This activity was conducted through a community empowerment approach with the Forest Farmers Group (KTH) in Patanyamang, utilizing Global Positioning System (GPS) technology. The GPS introduction training was led by practitioners from Bantimurung Bulusaraung National Park, followed by bamboo coordinate data collection involving local community members.The activity was divided into three groups based on hamlets, namely Mangai Hamlet, Bontotanga Hamlet, and Laelbata Hamlet. Each group was trained to use GPS devices to identify bamboo locations in their respective areas. The data collection results showed that the Mangai Hamlet group obtained 17 coordinate points, the Bontotanga Hamlet group obtained 8 points, and the Laelbata Hamlet group obtained 13 points. The use of GPS technology proved effective in mapping the distribution of bamboo, serving as an initial step in landslide disaster mitigation in the area. However, these coordinate points only reflect bamboo locations that are directly accessible. To acquire a more comprehensive distribution dataset, further analysis using satellite imagery or remote sensing is required. This activity provided benefits in enhancing the community’s capacity, especially in GPS technology utilization, and raised awareness of the importance of bamboo conservation as part of disaster mitigation efforts. Keywords: GPS Mapping, Bam